Courtyard of the Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
View of the Suswani Mata Temple from the north-western corner of the complex, in which the old shrine is centrally located and is surrounded by open spaces and rest houses constructed later. The sacred Kera tree and the Latina shikhara (mono-spired north Indian variety of temple superstructure) are also visible in the picture.